Struktur Komunitas Ikan di Perairan Sei Ladi Kelurahan Kampung Bugis Kota Tanjungpinang - Edo, Edo; Susiana, Susiana (Akuatiklestari, 2021)
Fish are vertebrates that live systematically in water and belong to the Phylum Chordata with the characteristics of having gills that function to take dissolved oxygen from the water and fins are used for swimming. The purpose of this study was to determine the structure of the fish community in Sei Ladi waters, Bugis Village, Tanjungpinang District, Riau Islands Province. This research method was carried out by direct observation at the location, interviews and fish identification. Data taken in this field practice are primary and secondary data. The results obtained with the diversity index value obtained were 1.94, so the diversity of fish in Sei Ladi was included in the medium category, the uniformity index value (E) of fish species in Sei Ladi waters was 0.88, close to 1, which means that each The species are relatively the same, the dominance index value (C) of fish species in Sei Ladi waters is 0.17, which means that there is no fish species that dominates in these waters.